2022
DOI: 10.1021/acs.jpclett.2c01458
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamically Driven Formation of Intercalated Cu Carpets from Supported Cu Pyramids on MoS2

Abstract: Thermodynamic and kinetic analyses based on our first-principles density functional theory calculations are used to interpret the experimentally observed formation of Cu carpets intercalated under the top layer of a 2H-MoS 2 substrate. Spontaneous Cu transport from Cu pyramids on top of the MoS 2 substrate through surface point defects to the growing Cu carpet is shown to be driven by a slightly lower chemical potential for the Cu carpet. We demonstrate that the competition between a preference for a thicker C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Note that the successful synthesis of Cu clusters on MoS 2 -based substrates with point defects has been experimentally demonstrated. [44][45][46][47] These experimental ndings greatly inspired us further to explore the catalytic performance of such systems in the CO 2 ER.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the successful synthesis of Cu clusters on MoS 2 -based substrates with point defects has been experimentally demonstrated. [44][45][46][47] These experimental ndings greatly inspired us further to explore the catalytic performance of such systems in the CO 2 ER.…”
Section: Resultsmentioning
confidence: 99%
“…To address this issue, herein, we carried out a systematic density functional theory (DFT) study on the design of Cu-based clusters anchored on a defective molybdenum disulde (MoS 2 ) monolayer with sulfur (S) vacancies as effective and highly selective catalysts for the reduction of CO 2 to C 2 H 4 . Notably, S vacancies can naturally occur during the preparation of the MoS 2 monolayer, [41][42][43] and have been widely employed as substrates for anchoring various SCMs, such as Cu, [44][45][46][47] Ag, 48 and Pt clusters. 49,50 Especially, MoS 2based materials have been proposed as efficient catalysts for CO 2 electrochemical reduction, including the anchored SACs and the exposed edges, in which some C 1 products can be obtained, such as CO, CH 4 , and CH 3 OH.…”
Section: Introductionmentioning
confidence: 99%
“…[142] For example, Han et al have demonstrated the formation of intercalated Cu carpets within MoS 2 via a vacancy-mediated atomic diffusion strategy. [143] Up to now, a myriad of approaches have been developed for the atomic intercalation of various non-noble metals spanning Fe, [144] Co, [145] Sn, [146,147] Cu, [148] etc. In this respect, it is theoretically feasible to integrate non-noble metal optical antennas within 2DLMs through atomic intercalation techniques to improve their interaction with the incident light.…”
Section: Non-noble Metal Optical Antenna Promoted 2dlm Photodetectorsmentioning
confidence: 99%
“…[1][2][3][4][5] Often, properties are changed by physical doping or intercalation of metal or other atoms. [6][7][8][9][10][11] Another class of layered materials involves aluminosilicates. Again, for these materials, there is interest in manipulating structure and properties, which for these systems can be achieved by chemical reaction with a pillaring agent.…”
Section: Introductionmentioning
confidence: 99%